Progression of White Matter Lesion Volume and Health-Related Quality of Life in Patients with Symptomatic Atherosclerotic Disease: The SMART-MR Study. (16th October 2011) - Grool, Anne M.; van der Graaf, Yolanda; Witkamp, Theo D.; Vincken, Koen L.; Mali, Willem P. T. M.; Geerlings, Mirjam I.
Abstract : Objectives . Mechanisms influencing the course of physical and mental functioning after an atherosclerotic event are unclear. We examined effects of white matter lesion (WML) activity on changes in functioning in patients with symptomatic atherosclerotic disease. Methods . In 486 patients (58 ± 9 years) of the Second Manifestations of ARTerial disease-Magnetic Resonance (SMART-MR) study, volumetric WML measurements on 1.5T MRI were performed at baseline and3.9 ± 0.4 years followup. Functioning was assessed with the modified Short-Form 12 (SF-12) questionnaire. Associations of WML progression with changes in functioning were adjusted for age, sex, and vascular risk factors. Results . Physical functioning (baseline: 44, 10th–90th percentile 29–55) improved, whereas mental functioning (baseline: 51, 10th–90th percentile 32–60) declined during followup. WML progression (highest quartile versus rest) contributed to a stronger decline in mental functioning (B = − 1.76, 95% CI −3.11 to −0.42), but did not influence changes in physical functioning. Conclusions . Progression of WML volume contributes to a decline in mental functioning in patients with symptomatic atherosclerotic disease.